Positive association of ethylene oxide levels with young stroke: a population-based study - Le, Lingying; Lan, Ziwei; Chen, Chenxi (Frontiers in Aging Neuroscience, 2024)
Background: Ethylene oxide (EtO), a highly reactive organic compound with extensive industrial applications, poses significant health risks. The association between EtO exposure and stroke was not well established. This study examined the association between EtO exposure and stroke among US adults using data from the 2013-2018 National Health and Nutrition Examination Survey (NHANES). Methods: We used appropriately weighted multifactorial logistic regression models to analyze the data and validated the findings with smoothed curve fitting. Stratified analysis and interaction assessments were performed to evaluate the robustness of the findings.Results: The study included 5,071 participants, balanced between men and women, with a stroke prevalence of 4.1%. Higher EtO levels were associated with rising rates of stroke (OR=1.23, 95% CI: 1.06-1.42). Individuals in the top 25% group displayed a stroke prevalence 1.6 times higher than those in the bottom 25% group (OR=1.60, 95%CI: 1.03-2.48). Stratified analysis demonstrated a significant positive association between EtO and stroke in individuals under 50 years (OR=1.94, 95%CI: 1.38-2.72), while no significant association was found in those aged 50 and above (OR=0.97, 95%CI: 0.83-1.14).This study identified a significant association between EtO exposure and stroke occurrence in young adults in the United States.